Poetic style and innovation in Old English, Old Norse, and Old Saxon - Hartman, Megan E. (Richard Rawlinson Center series for Anglo-Saxon studies, 2020)
This book traces the development of hypermetric verse in Old English and compares it to the cognate traditions of Old Norse and Old Saxon. The study illustrates the inherent flexibility of the hypermetric line and shows how poets were able to manipulate this flexibility in different contexts for different practical and rhetorical purposes. This mode of analysis is therefore able to show what degree of control the poets had over the traditional alliterative line, what effects they were able to produce with various stylistic choices, and how attention to poetic style can aid in literary analysis